Fine-Tuning of Photosynthesis Requires CURVATURE THYLAKOID1-Mediated Thylakoid Plasticity. Issue 3 (26th January 2018) - Pribil, Mathias; Sandoval-Ibáñez, Omar; Xu, Wenteng; Sharma, Anurag; Labs, Mathias; Liu, Qiuping; Galgenmüller, Carolina; Schneider, Trang; Wessels, Malgorzata; Matsubara, Shizue; Jansson, Stefan; Wanner, Gerhard; et al.
Abstract : The CURT1A component of the CURT1 protein complex mediates thylakoid membrane curvature and modulates photosynthesis to maintain plant fitness during fluctuating environmental conditions. Abstract: The thylakoid membrane system of higher plant chloroplasts consists of interconnected subdomains of appressed and nonappressed membrane bilayers, known as grana and stroma lamellae, respectively. CURVATURE THYLAKOID1 (CURT1) protein complexes mediate the shape of grana stacks in a dosage-dependent manner and facilitate membrane curvature at the grana margins, the interface between grana and stroma lamellae. Although grana stacks are highly conserved among land plants, the functional relevance of grana stacking remains unclear. Here, we show that inhibiting CURT1-mediated alteration of thylakoid ultrastructure in Arabidopsis ( Arabidopsis thaliana ) reduces photosynthetic efficiency and plant fitness under adverse, controlled, and natural light conditions. Plants that lack CURT1 show less adjustment of grana diameter, which compromises regulatory mechanisms like the photosystem II repair cycle and state transitions. Interestingly, CURT1A suffices to induce thylakoid membrane curvature in planta and thylakoid hyperbending in plants overexpressing CURT1A. We suggest that CURT1 oligomerization is regulated at the posttranslational level in a light-dependent fashion and that CURT1-mediated thylakoid plasticity plays an important role in fine-tuning photosynthesis and plant fitness during challenging growth conditions.